A Bibliometric Analysis of Jaggery Related Literature Published During 2000-2023 - Kamboj, Sachin; Tyagi, Sudhir Kumar (Journal of Data Science, Informetrics, and Citation Studies)
The study proposed to provide a bibliometric analysis of the jaggery-related literature published from 2000 to 2023. The data for this study was retrieved from the Scopus database and analyzed using VOSviewer, Bibliometrix, and word cloud for the following: trend of publications, type of document, h-index, performance of countries and authors, most cited publications and most prolific journals. Further, a co-authorship network of countries and authors, a co-citation network of authors and references, a co-occurrence network, word clouds of keywords, and a thematic map were also analyzed to find research hot spots and current and future directions of research. Results showed that India, Colombia, and Pakistan are the leading producers of scientific literature while Sugar Tech and Journal of Food Science and Technology are the most influential journals in this field. A Co-authorship network indicates a low level of cooperation among the countries and the researchers, which is not conducive to the progress of research in the field. Word cloud and thematic map show that research related to jaggery is moving in a diversified direction. It is anticipated that this bibliometric study will be crucial to the researchers' understanding of research trends, hotspots, advancements, and current and future directions.
Keywords: Bibliometric analysis; VOSviewer; Bibliomterix; Non-centrifugal sugar; Sugarcane; Jaggery.